Self-Rehabilitation of a Captive American Crow at Binghamton Zoo. Issue 3 (3rd July 2017) - Davie, Clara; Clark, Anne B.
ABSTRACT: The behavioral transition from an entirely unflighted-to-flighted, female yearling American crow ( Corvus brachyrhynchos ) in captivity in a specially designed exhibit was documented at the Binghamton Zoo at Ross Park in Binghamton, NY. Upon arrival, the focal crow had no complete primary feathers or retrices and had been in captivity since fledging. She apparently had never flown successfully and was using her legs and an abnormal body orientation to cushion her landing on the ground. In a social and physical environment with 3 flying companion crows and staggered perches, she developed and appeared to "practice" routines that ultimately resulted in her recovering normal body posture and flight ability. The crow's practice routine was recorded during daily observations using an ethogram of social and locomotor behaviors. Both enclosure design and the social environment may have provided an ideal setting for the self-motivation of practice and this recovery. Attention to the potential for such practice could facilitate rehabilitation in individuals for whom rehabilitation was not thought possible.